Pre- and Early Post-treatment With Arthrospira platensis (Spirulina) Extract Impedes Lipopolysaccharide-triggered Neuroinflammation in Microglia - Piovan, Anna; Battaglia, Jessica; Filippini, Raffaella; Dalla Costa, Vanessa; Facci, Laura; Argentini, Carla; Pagetta, Andrea; Giusti, Pietro; Zusso, Morena (Frontiers in Pharmacology, 2021)
Background: Uncontrolled neuroinflammation and microglia activation lead to cellular and tissue damage contributing to neurodegenerative and neurological disorders. Spirulina (Arthrospira platensis (Nordstedt) Gomont, or Spirulina platensis), a blue-green microalga, which belongs to the class of cyanobacteria, has been studied for its numerous health benefits, which include anti-inflammatory properties, among others. Furthermore, in vivo studies have highlighted neuroprotective effects of Spirulina from neuroinflammatory insults in different brain areas. However, the mechanisms underlying the anti-inflammatory effect of the microalga are not completely understood. In this study we examined the effect of pre- and post-treatment with an acetone extract of Spirulina (E1) in an in vitro model of LPS-induced microglia activation. Methods: The effect of E1 on the release of IL-1β and TNF-α, expression of iNOS, nuclear factor erythroid 2–related factor 2 (Nrf2), and heme oxygenase-1 (HO-1), and the activation of NF-κB was investigated in primary microglia by ELISA, real-time PCR, and immunofluorescence. Results: Pre- and early post-treatment with non-cytotoxic concentrations of E1 down-regulated the release of IL-1β and TNF-α, and the over-expression of iNOS induced by LPS. E1 also significantly blocked the LPS-induced nuclear translocation of NF-κB p65 subunit, and upregulated gene and protein levels of Nrf2, as well as gene expression of HO-1. Conclusions: These results indicate that the extract of Spirulina can be useful in the control of microglia activation and neuroinflammatory processes. This evidence can support future in vivo studies to test pre- and post-treatment effects of the acetone extract from Spirulina.